The most wonderful animals that never were - Krutch, Joseph Wood, 1893-1970. (Boston : Houghton Mifflin, 1969)
Relates the legends of nonexistent animals like the unicorn and phoenix as well as how folklore arose about real animals such as the crocodile, salamander, ostrich and others.
Keywords: Animals -- Folklore